Effects of seasonal acclimation on cold tolerance and biochemical status of the carob moth, Ectomyelois ceratoniae Zeller, last instar larvae. Issue 5 (13th May 2014) - Heydari, M.; Izadi, H.
Abstract: The carob moth, Ectomyelois ceratoniae, a pest of Punica granatum, overwinters as a larva. In this study, physiological changes, water content, cold hardiness and supercooling points (SCPs) in relation to ambient temperature in the overwintering period (October to March) and changes of these factors between diapausing (February) and non-diapausing (September) larvae were studied. Pupae that were derived from diapausing larvae (April) and  from non-diapausing larvae (August) were also compared. Total body sugar, lipid and protein contents increased with decrease in the temperature and reached the highest levels (12.82, 1.99 and 6.11 mg g −1 body weight, respectively) in February, but glycogen content decreased and reached the lowest level (1.12 mg g −1 body weight) in February. There were significant differences in the levels of these compounds between diapausing and non-diapausing larvae, and pupae that were derived from diapausing and non-diapausing larvae. Trehalose and myo-inositol contents increased during diapause and reached the highest levels (0.50 and 0.07 mg g −1 body weight, respectively) in February. There were significant differences in the levels of these compounds between diapausing and non-diapausing larvae, but the differences between pupae that were derived from diapausing and non-diapausing larvae were not significant. The SCP of diapausing larvae (−17.3 °C) was significantly lower than in the non-diapausing larvae (−12.0 °C). SCP decreased gradually in autumn and reached the lowest level in the middle of winter. Changes of cold hardiness were inversely proportional to SCP changes. The lowest levels of water (65%) and weight (43.13 mg) were recorded in January and March, respectively. Most probably, lipids play a role as energy reserve, and low-molecular weight carbohydrates and polyols provide cryoprotection for overwintering larvae of the carob moth. Since the overwintering larvae die at temperatures above the SCP, the carob moth larvae were found to be a chill-intolerant insect.